Potential impact of current agricultural practices on mycotoxin occurrence and mycotoxin knowledge along the cassava value chain in Uganda - Oyesigye, E.; Cervini, C.; Mahuku, G.; Medina, A. (Elsevier, 2024)
Cassava is the second most important staple food crop for Uganda and is prone to contamination with mycotoxins. This study aimed at understanding the current agricultural practices, their potential influence on mycotoxin occurrence, as well as assessing mycotoxin knowledge among key cassava value chain actors, including farmers, wholesalers, and processors. Data were collected through individual interviews (210), key informant interviews (34), and 4 focus group discussions. The findings revealed that 51% of farmers peeled cassava directly on bare ground, resulting in direct contact with soil that potentially harbors mycotoxin-producing fungi, such as Aspergillus section Flavi. During postharvest handling, 51.6% of farmers dried cassava chips directly on bare ground. Nearly, all (95.2%) of wholesalers packed cassava chips in local gunny bags and placed them on ground instead of pallets. In the processing of cassava chips into flour, only one of the 14 processing machines was certified by the Uganda National Bureau of Standards. Additionally, there was only one processing machine available for every 180 (1:180) consumers bringing their cassava for processing. 50.8% of cassava consumers interviewed admitted to consuming cassava flour regardless of quality, while 73% blended cassava flour with flour from mycotoxin-susceptible crops mainly maize, millet, and sorghum. Most (96.2%) of the people along the cassava value chain did not understand what the term mycotoxins meant. However, 56% of interviewed respondents were familiar with the term aflatoxins. Of the cassava value chain actors aware of mycotoxins, 82.9% knew of methods for reducing aflatoxin contamination, but only 40.9% were putting such methods into practice. More farmers (47.9%) managed aflatoxins compared to wholesalers (33.3%) and processors (21.4%). Knowledge on aflatoxins was significantly associated with value chain actor (P = 0.026), head of household (P = 0.004), region (P = 0.033), age (P = 0.001), and experience (P = 0.001). This study highlights the critical areas of mycotoxin contamination within the cassava value chain in Uganda and underscores the need to improve the knowledge among value chain actors especially farmers.